Design of miniature pulsatile pump - Yodo, William (2015)
In this project, the existing pump and its mechanism have been developed to make a double reciprocating ball pump (DRBP) feasible. Several designs of the DRBP are considered and explored and the final design of DRBP is proposed. The design of the DRBP is simple and easy to fabricate. Besides that, the pump can deliver the fluid with minimum contamination. The working principle of the DRBP is presented to gain more understanding while it is operating. The DRBP working principle is unique and does not require any valve to regulate. In addition, several mechanisms of the double reciprocating ball mechanism are discussed and presented to produce the desired movement and the final design mechanism for DRBP is proposed. The functionality of two sizes of DRBP (Ball Ø 5mm, type 1 and Ball Ø 3mm, type 2) has been verified by experimental studies. The experimental studies have been conducted successfully using water as the working fluid. The experimental studies show the basic behaviours of the DRBP in terms of several parameters such as instantaneous flow rate and differential pressure. The DRBP works smoothly for various spm (stroke length per minute). The DRBP type 1 can produce average flow rate of 200, 188, 170 ml/min with 100,110,120 spm respectively. Moreover, the DRBP type 2 yields average flow rate of 120, 110, 106 ml/min with 100,110,120 spm respectively.